PENGARUH SUDUT INKLINASI DAN JENIS BAHAN TERHADAP DAYA KELUARAN DAN EFISIENSI MODUL SURYA SKALA MIKRO DENGAN DUA REFLEKTOR - Nurhakiki, Mauludiya Annisa; Wibawa, Unggul; Hasanah, Rini Nur (Jurnal Mahasiswa TEUB, 2024)
Two sided reflectors are reflectors that face each other with the function of focusing sunlight so that they fall directly on the solar module. The usage of two reflector units is intended to make the output power and efficiency of the module higher than if using a single-sided reflector but not to cover the incident light area like using a three or four-sided reflectors. The inclination angles used were 30˚, 45˚, 60˚, 75˚, and 90˚ with reflector materials such as glass mirror, aluminum, and HVS paper. The results showed that the initial peak power and efficiency were 14.33W and 6.62%. The peak power and efficiency using a mirror reflector were 19.27W and 8.97% when the inclination angle was 60˚. The peak power and efficiency using the aluminum reflector were 18.59W and 8.67% when the inclination angle was 60˚. The peak power and efficiency using the HVS reflector were 15.23W and 7.10% at an inclination angle of 60˚. In addition, temperature and load levels relationship curves were also obtained for the operation of the 20WP micro-scale solar module. It can be deducted that the addition of double-sided mirror and aluminum reflectors with inclination angle of 60˚ increases the output power and efficiency of the solar module significantly and no special pattern is formed between temperature and load levels of the circuit for the various treatments tested. Keyword : solar module, inclination angle, reflector, output power, efficiency